Penjatuhan Sanksi Administrasi Bagi Prajurit Tentara Nasional Indonesia - Maxyenty Maxyenty; Salmon Eliazer Marthen Nirahua; Renny Heronia Nendissa (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Violations committed by members of the TNI will affect the good name of the unit and the development of personnel in the unit. Purposes of the Research: Legal issues in this study is how the procedure for administering administrative sanctions for TNI soldiers? and How is the legal protection for TNI soldiers who committed a violation in accordance with the substance of the TNI administrative sanction? As for the purpose.Methods of the Research: This research is to find out and analyze the procedures for imposing sanctions administration for TNI soldiers to find out and analyze legal protection for TNI soldiers who commit violations in accordance with the substance of administrative sanctions for the provision of administrative sanctions for TNI soldiers This study uses normative legal research that is description with a statute approach and Conceptual approach (conceptual approach), through the collection of legal materials then analyzed by qualitative analysis.Results of the Research: Through this research it was found that there are procedures in the imposition of sanctions applied to the classification is classified prayer is a class of violations whose administrative sanctions are adjusted with his group, and his position is one of the things that distinguishes administrative sanctions such as administrative sanctions for officers will be different with a non-commissioned officer / enlisted. and legal protection of soldiers who will be dropped administrative sanctions can be realized by the application of sanctions based on the the principle of fair law, as has been stated, namely the principle of educating, the principle of Openness, the principle of balance, the principle of justice, the principle of equality.